Employment Inequalities Among British Minority Ethnic Workers in Health and Social Care at the Time of Covid-19: A Rapid Review of the Literature. Issue 2 (April 2022) - Hussein, Shereen
Abstract : There are long-standing concerns of inequalities in the workplace among minority ethnic (ME) workers in the UK health and social care (H&SC) sectors. ME workers contribute significantly to H&SC delivery. However, there is considerable evidence of substantial negative experiences among this group across various workplace indicators and outcomes, including (mis)treatment. The COVID-19 pandemic has exacerbated these inequalities with higher infection rates and related deaths among ME health and care workers. A rapid review methodology was employed to examine the work experiences and outcomes of ME workers in H&SC in the UK, focusing on low paid workers. The review identified fifty-one relevant outputs, detailing the nature and extent of inequalities across recruitment, career progression and treatment at work, including bullying and harassment. The findings highlight the impact of the intersectionality of gender, race and migration status concerning the ways inequalities are manifested and operated through individual perceptions and institutional and structural racism.